Preparation method of SCR (Selective Catalytic Reduction) denitration catalyst
By synthesizing cerium-silicon composite nanoparticles on the surface of single-layer graphene oxide and synthesizing zinc-based metal organic framework on the surface of carbon fiber, forming a composite gel and metal nitrate composite and adsorbing into the porous structure of nickel foam, the existing solution is solved The SCR denitrification catalyst has poor selectivity and insufficient resistance under medium and low temperature conditions, achieving efficient and stable medium and low temperature denitrification effect.
Patent Information
- Application Number
- CN202510033509.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing SCR denitrification catalysts have poor selectivity for nitrogen under medium and low temperature conditions, and have poor sulfur resistance and water resistance, which leads to the catalyst being easily deactivated and increases the operating cost of the denitrification process.
cerium-silicon composite nanoparticles are synthesized on the surface of a single layer of graphene oxide, and zinc-based metal organic framework is synthesized on the surface of carbon fiber to form a composite gel and metal nitrate composite, adsorbed into the porous structure of nickel foam, forming lignin intersecting Connect network structure to improve the active site and dispersion of the catalyst.
It improves the medium and low temperature denitrification efficiency of the catalyst, enhances the sulfur resistance and water resistance of the catalyst, extends the service life of the catalyst, and improves the mechanical strength.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of denitration catalysts, and in particular to a method for preparing a SCR denitration catalyst. Background Art
[0002] Nitrogen oxides are collectively referred to as NO x It is one of the main sources of air pollution. The main sources include fixed sources and mobile sources. Fixed sources mainly include thermal power, glass, ceramics, cement, steel and other industries, and mobile sources mainly include motor vehicles and non-road machinery. Excessive NO x It can cause a series of environmental problems such as acid rain, ozone layer depletion and photochemical smog, and is toxic to human health and plants. The ammonia selective catalytic reduction of nitrogen oxides (SCR) technology is considered to be one of the most effective technologies for controlling nitrogen oxide pollution. In the SCR reaction, the reducing agent is a substance that selectively reacts chemically with nitrogen oxides in the flue gas at a certain temperature.
[0003] SCR denitrification catalyst can effectively remove nitrogen oxides from flue gas, but the reaction activity temperature range of SCR denitrification catalyst is relatively high, which increases the operating cost of the denitrification process. Therefore, there is an urgent need to develop highly active low-temperature denitrification SCR catalysts; the use of medium and low temperature SCR denitrification catalysts has the characteristics of low reaction temperature and high catalytic activity, but the medium and low temperature SCR denitrification catalysts have poor selectivity for nitrogen under medium and low temperature conditions, and poor sulfur resistance and water resistance, which makes the denitrification catalyst easily deactivated during the denitrification process. Summary of the invention
[0004] The invention aims to provide a method for preparing an SCR denitration catalyst: synthesizing cerium-silicon composite nanoparticles on the surface of a monolayer graphene oxide, thereby improving the binding force of cerium oxide on the monolayer graphene oxide, and the synthesized nano-scale cerium-silicon composite particles have a high surface area, thereby improving the active sites of the denitration catalyst; synthesizing a zinc-based metal organic skeleton on the surface of a pretreated carbon fiber, thereby improving the contact area between the carbon fiber and the active component, and the synthesized zinc-based metal organic skeleton has a large porosity, thereby increasing the contact area with nitrogen oxides and improving the denitration efficiency of the denitration catalyst; modified graphene oxide, modified carbon fiber, lignin, acrylic acid and a cross-linking agent are mixed and reacted to form a composite gel, thereby improving the dispersibility of the modified graphene oxide and the modified carbon fiber in the denitration catalyst; the composite gel is composited with a metal nitrate to form a slurry, which is adsorbed into the porous structure of the nickel foam, and the formed lignin cross-linked network structure contains a large number of hydroxyl sites, thereby providing adsorption sites for the active components in the metal nitrate, so that the active components are uniformly dispersed on the composite gel, thereby enhancing the contact area between the catalyst and the nitrogen oxides.
[0005] The technical problem to be solved by the present invention is as follows: SCR denitration catalyst can effectively remove nitrogen oxides in flue gas, but the reaction activity temperature range of SCR denitration catalyst is relatively high, which increases the operating cost of the denitration process. Therefore, it is urgent to develop a high-activity low-temperature denitration SCR catalyst; the use of medium and low temperature SCR denitration catalyst has the characteristics of low reaction temperature and high catalytic activity, but the medium and low temperature SCR denitration catalyst has poor selectivity for nitrogen under medium and low temperature conditions, and poor sulfur resistance and water resistance, which causes the denitration catalyst to be easily deactivated during the denitration process.
[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing an SCR denitration catalyst comprises the following steps: S1. Mixing the composite gel, the metal nitrate complex and deionized water, stirring to obtain a slurry; S2. The pretreated nickel foam is impregnated into the slurry, the temperature is raised to 30-40°C, stirred at 500-600r / min for 2-4h, calcined, and cooled to room temperature to obtain an SCR denitration catalyst.
[0007] Furthermore, in step S1, the ratio of the composite gel, the metal nitrate complex and the deionized water is (5-6) g: (4-5) g: (100-120) mL.
[0008] Furthermore, in step S1, the metal nitrate complex is prepared by mixing manganese nitrate and copper nitrate in a mass ratio of (0.5-1.5):(4-5).
[0009] Furthermore, in step S2, the calcination temperature is 700-800°C, and the calcination time is 5-8h.
[0010] Further, the pretreated nickel foam is specifically prepared by the following steps: The nickel foam is soaked in an acetone solution for 10-20 minutes, taken out, washed, and then soaked in dilute hydrochloric acid with a concentration of 2-4 mol / L for 10-20 minutes, taken out, washed, and dried to obtain a pretreated nickel foam.
[0011] Among them, acetone treatment of nickel foam can effectively remove grease, oil stains and other organic impurities on the surface of nickel foam, and dilute hydrochloric acid can react with the oxide layer on the surface of nickel foam to remove the oxide layer, which is beneficial to the mixed adsorption of nickel foam and slurry.
[0012] Furthermore, the porosity of nickel foam is 94-96%, the pore size is 0.1-0.2 mm, and the volume density is 0.4-0.6 g / cm 3 .
[0013] Furthermore, the composite gel is obtained by a mixed reaction of modified graphene oxide, modified carbon fiber, initiator, acrylic acid, lignin and a cross-linking agent.
[0014] Furthermore, the initiator is ammonium persulfate.
[0015] Furthermore, the cross-linking agent is N,N-methylenebisacrylamide.
[0016] Furthermore, the composite gel is specifically prepared by the following steps: Potassium hydroxide was added to deionized water and stirred evenly. Acrylic acid, a crosslinking agent and an initiator were added. After stirring for 10 minutes, lignin, modified graphene oxide and modified carbon fiber were added. The temperature was raised to 75°C, ultrasonicated at 50KHz for 3 hours, and dried in an oven at 70°C for 20 minutes to obtain a composite gel.
[0017] Furthermore, the carboxyl group of acrylic acid is chemically bonded to the hydroxyl group of lignin, and under the action of an initiator, acrylic acid and a cross-linking agent N,N-methylenebisacrylamide are copolymerized to form a cross-linked network structure. The hydroxyl group contained in lignin can also be chemically bonded to the oxygen-containing functional groups on the surface of modified graphene oxide and modified carbon fiber, so that the modified graphene oxide and modified carbon fiber are evenly distributed in the cross-linked network structure of lignin to form a composite gel.
[0018] Furthermore, the amount ratio of potassium hydroxide, deionized water, acrylic acid, crosslinking agent, initiator, lignin, modified graphene oxide and modified carbon fiber is (4-6) g: (45-55) mL: (2-4) mL: (0.05-0.15) g: (0.05-0.15) g: (2-3) g: (1-2) g: (1-3) g.
[0019] Furthermore, the modified graphene oxide is obtained by ultrasonically exfoliating graphene oxide, mixing it with ethyl silicate and cerium chloride heptahydrate, and then sintering it.
[0020] Furthermore, the particle size of graphene oxide is 0.1-2 μm.
[0021] Furthermore, the ultrasonic power is 40-60 KHz, and the ultrasonic time is 20-40 min.
[0022] Furthermore, the sintering temperature is 450-550° C., and the sintering time is 4-6 hours.
[0023] Further, the modified graphene oxide is specifically prepared by the following steps: A1. Add graphene oxide to deionized water, stir evenly, place in a 50°C water bath, ultrasonically treat at 50KHz for 30 minutes, filter, wash with deionized water three times, and dry in a 70°C oven for 10 minutes to obtain a single layer of graphene oxide; A2. Add cerium chloride heptahydrate and ethyl silicate to deionized water and ethanol, stir evenly, add monolayer graphene oxide and sodium hydroxide, stir at 250r / min for 35min, place in a reactor, stir and react at 120°C for 7h, cool to room temperature, take out, place in a sintering furnace, sinter at 500°C for 5h, cool to room temperature to obtain modified graphene oxide.
[0024] Furthermore, during the above-mentioned reaction A1, under the action of ultrasound, graphene oxide can weaken the forces between graphene oxide sheets, so that graphene oxide is peeled off to form a single-layer graphene oxide. The formed single-layer graphene oxide has abundant active sites and a large number of defect structures, which is conducive to the in-situ synthesis of uniformly distributed cerium-silicon composite nanoparticles on the surface of graphene oxide.
[0025] Furthermore, in the above-mentioned reaction process A2, the oxygen-containing functional groups contained on the surface of the monolayer graphene oxide can be combined with the cerium ions in the cerium chloride heptahydrate through chemical bonds, so that the cerium ions are deposited on the surface of the monolayer graphene oxide, and the cerium ions can also be combined with the hydroxide ions in the sodium hydroxide, and the formed hydroxide is deposited on the surface of the monolayer graphene oxide, and reacts at 120° C., so that the hydroxide deposited on the surface of the monolayer graphene oxide is thermally decomposed to form an oxide, and as the reaction proceeds, the oxide crystals grow to form nano-cerium oxide, thereby forming nano-cerium oxide particles on the surface of the monolayer graphene oxide; Furthermore, during the reaction, the silica network structure formed by the hydrolysis and cross-linking of ethyl silicate can also combine with the cerium ions through chemical bonds, so that the silica network structure is deposited on the surface of the single-layer graphene oxide, and sintered at 500-600°C, so that the cerium-silicon composite nanoparticles uniformly distributed are synthesized in situ on the surface of the graphene oxide.
[0026] Furthermore, in step A1, the ratio of graphene oxide to deionized water is (1-2) g:(45-55) mL.
[0027] Furthermore, in step A2, the ratio of cerium chloride heptahydrate, ethyl silicate, deionized water, ethanol, monolayer graphene oxide and sodium hydroxide is (6-7) g: (5-7) g: (75-85) mL: (15-25) mL: (5-6) g: (2-3) g.
[0028] Furthermore, the modified carbon fiber is prepared by surface-modifying the carbon fiber with dopamine and then reacting the carbon fiber with a zinc source, 2-aminobenzothiazole and 2-methylimidazole dimethylimidazole.
[0029] Furthermore, the zinc source is selected from any one of zinc nitrate hexahydrate, zinc chloride and zinc acetate.
[0030] Furthermore, the carbon fibers are 1-3 μm long and 20-30 nm in diameter.
[0031] Further, the modified carbon fiber is specifically prepared by the following steps: B1. Add the carbon fiber to Tris-HCl buffer with a pH of 8.5, stir evenly, add dopamine, stir for 4 hours, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10 minutes to obtain pretreated carbon fiber; B2. Add zinc source, 2-aminobenzothiazole and 2-methylimidazole to methanol, stir evenly, add sodium formate and pretreated carbon fiber, stir evenly, introduce nitrogen, react at 60°C for 4 hours, centrifuge at 8000r / min, wash 3 times with methanol, wash 3 times with deionized water, and dry in an oven at 60°C for 10 minutes to obtain modified carbon fiber.
[0032] Furthermore, during the above reaction B1, in the Tris-HCl buffer, dopamine can self-polymerize on the surface of the carbon fiber to form polydopamine, so that the carbon fiber carries a large number of phenolic hydroxyl groups, which is beneficial to the synthesis of a zinc-based metal organic framework on the surface of the carbon fiber.
[0033] Furthermore, in the above-mentioned B2 reaction process, zinc ions in the zinc source can combine with oxygen-containing functional groups on the surface of the pretreated carbon fiber, so that the zinc ions are deposited on the surface of the pretreated carbon fiber. 2-Methylimidazole and 2-aminobenzothiazole serve as organic ligands, and the zinc ions react with the organic ligands to form a three-dimensional network structure of a zinc-based metal organic skeleton, so that the zinc-based metal organic skeleton is deposited on the surface of the pretreated carbon fiber to obtain modified carbon fiber.
[0034] Furthermore, in step B1, the ratio of carbon fiber, Tris-HCl buffer and dopamine is (1-2) g: (50-60) mL: (0.6-0.8) g.
[0035] Furthermore, in step B2, the ratio of zinc source, 2-aminobenzothiazole, 2-methylimidazole, methanol, sodium formate and pretreated carbon fiber is (1.6-2) g: (1-2) g: (2-3) g: (75-85) mL: (1-1.4) g: (5-6) g.
[0036] Furthermore, compared with the prior art, the present invention has the following beneficial effects: (1) In the technical scheme of the present invention, the single-layer graphene oxide formed by ultrasonic treatment of graphene oxide has abundant active sites and a large number of defect structures, which is conducive to the in-situ synthesis of uniformly distributed cerium-silicon composite nanoparticles on the surface of the single-layer graphene oxide; the cerium-silicon composite nanoparticles are synthesized on the surface of the single-layer graphene oxide. On the one hand, the cerium-silicon composite nanoparticles formed on the surface of the single-layer graphene oxide, silicon dioxide and cerium oxide are chemically bonded, which improves the binding force of cerium oxide on the single-layer graphene oxide, and the single-layer graphene oxide, as a carrier of cerium-silicon composite nanoparticles, can load a large amount of cerium-silicon composite nanoparticles, thereby improving the denitration efficiency of the denitration catalyst. On the other hand, the synthesized nanoscale cerium-silicon composite particles have a high surface area, which increases the active sites of the denitration catalyst and provides new active sites, which helps to adsorb NO and NH3, thereby improving the denitration efficiency and also prolonging the service life of the catalyst. In addition, the cerium oxide particles in the cerium-silicon composite nanoparticles have a high catalytic reaction activity at medium and low temperatures, thereby improving the denitration efficiency of the denitration catalyst at medium and low temperatures.
[0037] (2) In the technical scheme of the present invention, dopamine can self-polymerize on the surface of carbon fiber to form polydopamine, so that the carbon fiber carries a large number of phenolic hydroxyl groups, which is beneficial to the synthesis of zinc-based metal organic skeleton on the surface of carbon fiber. On the one hand, the synthesis of zinc-based metal organic skeleton on the surface of carbon fiber improves the roughness of the carbon fiber surface and increases the contact area between the carbon fiber and the active component. The synthesized zinc-based metal organic skeleton has a large porosity, which increases the contact area with nitrogen oxides and improves the denitration efficiency of the denitration catalyst. On the other hand, the synthesized zinc-based metal organic skeleton has a high adsorption performance for metal ions in metal nitrates and can adsorb metal ions in metal nitrates onto the zinc-based metal organic skeleton, avoiding the shedding of metal active components and improving the service life of the denitration catalyst. The coordination bonds in the zinc-based metal organic skeleton can absorb and weaken the stress generated by external pressure, thereby improving the mechanical strength of the denitration catalyst.
[0038] (3) In the technical solution of the present invention, modified graphene oxide, modified carbon fiber, lignin, acrylic acid and a cross-linking agent are mixed and reacted to form a composite gel, which improves the dispersibility of modified graphene oxide and modified carbon fiber in the denitrification catalyst. The formed composite gel is combined with metal nitrate to form a slurry, which is adsorbed into the porous structure of the nickel foam. The formed lignin cross-linked network structure contains a large number of hydroxyl sites, which provide adsorption sites for the active components in the metal nitrate, so that the active components are evenly dispersed on the composite gel, thereby enhancing the contact area between the catalyst and the nitrogen oxides.
[0039] (4) In the technical scheme of the present invention, after the slurry formed by the composite gel and the metal nitrate complex is adsorbed into the porous structure of the nickel foam, it is carbonized at high temperature, and the skeleton lignin of the composite gel is thermally decomposed to form a carbon-carbon network structure, which has high water resistance. The carbon elements formed by the thermal decomposition of lignin can also combine with metal ions and be distributed in the porous structure of the nickel foam in the form of metal carbides, thereby increasing the force on the active components and avoiding the migration and precipitation of the active components. In addition, the modified graphene oxide, the modified carbon fiber and the formed carbon-carbon network structure serve as the skeleton structure of the porous nickel foam, thereby improving the mechanical strength of the denitration catalyst. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The raw materials used in the embodiments of the present invention are as follows: Cerium chloride heptahydrate (purity 99%, Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.); ethyl silicate (purity 99%, Hubei Handafei Biotechnology Co., Ltd.); dopamine (purity 98%, Shenzhen Hengfeng Wanda Pharmaceutical Technology Co., Ltd.); Tris-HCl buffer (pH 8.5, Wuhan Desheng Biochemical Technology Co., Ltd.); zinc nitrate hexahydrate (purity 99.0%, Nanjing Chemical Reagent Co., Ltd.); 2-aminobenzothiazole (purity 98%, Wuhan Kemik Biomedical Technology Co., Ltd.); 2-methylimidazole (purity 98%, Shanghai Puzhen Biotechnology Co., Ltd.); acrylic acid (analytical grade, Tianjin Damao Chemical Reagent Factory); N,N-methylenebisacrylamide (analytical grade, Beijing Inokai Technology Co., Ltd.); lignin (analytical grade, Shanghai MacLean Biochemical Co., Ltd.).
[0042] The pre-treated nickel foam is specifically prepared by the following steps: The nickel foam was soaked in an acetone solution for 15 minutes, taken out, washed three times with deionized water, soaked in 3 mol / L dilute hydrochloric acid for 15 minutes, taken out, washed three times with deionized water, and dried in an oven at 60° C. for 10 minutes to obtain a pretreated nickel foam.
[0043] The porosity of nickel foam is 94-96%, the pore size is 0.1-0.2mm, and the volume density is 0.4-0.6g / cm 3 , Kunshan Guangshengjia New Materials Co., Ltd.
[0044] Example 1 The modified graphene oxide is prepared by the following steps: A1. Add 1.5 g of graphene oxide to 50 mL of deionized water, stir evenly, place in a 50°C water bath, ultrasonically treat at 50 KHz for 30 min, filter, wash with deionized water three times, and dry in a 70°C oven for 10 min to obtain a single layer of graphene oxide; A2. Add 6.5 g of cerium chloride heptahydrate and 6 g of ethyl silicate to 80 mL of deionized water and 20 mL of ethanol, stir evenly, add 5.5 g of single-layer graphene oxide and 2.5 g of sodium hydroxide, stir at 250 r / min for 35 min, place in a reactor, stir and react at 120°C for 7 h, cool to room temperature, take out, place in a sintering furnace, sinter at 500°C for 5 h, cool to room temperature, and obtain modified graphene oxide.
[0045] Comparative Example 1 The difference between this comparative example and Example 1 is that cerium-silicon composite nanoparticles are not synthesized on the surface of the monolayer graphene oxide, and the remaining steps and raw materials are the same as those in Example 1.
[0046] 1.5 g of graphene oxide was added to 50 mL of deionized water, stirred evenly, placed in a 50° C. water bath, and ultrasonically treated at 50 KHz for 30 min. The mixture was filtered, washed with deionized water for 3 times, and dried in an oven at 70° C. for 10 min to obtain modified graphene oxide.
[0047] Comparative Example 2 The difference between this comparative example and Example 1 is that ethyl silicate is not added, and the remaining steps and raw materials are the same as those in Example 1.
[0048] A1. Add 1.5 g of graphene oxide to 50 mL of deionized water, stir evenly, place in a 50°C water bath, ultrasonically treat at 50 KHz for 30 min, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain a single layer of graphene oxide; A2. Add 6.5 g of cerium chloride heptahydrate to 80 mL of deionized water and 20 mL of ethanol, stir evenly, add 5.5 g of single-layer graphene oxide and 2.5 g of sodium hydroxide, stir at 250 r / min for 35 min, place in a reactor, stir and react at 120 ° C for 7 h, cool to room temperature, take out, place in a sintering furnace, sinter at 500 ° C for 5 h, cool to room temperature, and obtain modified graphene oxide.
[0049] Example 2 The modified carbon fiber is prepared by the following steps: B1. Add 1.5 g of carbon fiber to 55 mL of Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.7 g of dopamine, stir for 4 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain pretreated carbon fiber; B2. Add 1.8 g zinc nitrate hexahydrate, 1.5 g 2-aminobenzothiazole and 2.5 g 2-methylimidazole to 80 mL methanol, stir evenly, add 1.2 g sodium formate and 5.5 g pretreated carbon fiber, stir evenly, introduce nitrogen, react at 60 ° C for 4 hours, centrifuge at 8000 r / min, wash 3 times with methanol, wash 3 times with deionized water, and dry in an oven at 60 ° C for 10 minutes to obtain modified carbon fiber.
[0050] Comparative Example 3 The difference between this comparative example and Example 2 is that the pretreated carbon fiber is replaced by carbon fiber, and the remaining steps and raw materials are the same as Example 2.
[0051] Add 1.8 g zinc nitrate hexahydrate, 1.5 g 2-aminobenzothiazole and 2.5 g 2-methylimidazole to 80 mL methanol, stir evenly, add 1.2 g sodium formate and 5.5 g carbon fiber, stir evenly, introduce nitrogen, react at 60 ° C for 4 h, centrifuge at 8000 r / min, wash 3 times with methanol, wash 3 times with deionized water, and dry in a 60 ° C oven for 10 min to obtain modified carbon fiber.
[0052] Comparative Example 4 The difference between this comparative example and Example 2 is that the zinc-based metal organic framework is not synthesized on the surface of the pretreated carbon fiber, and the remaining steps and raw materials are the same as those in Example 2.
[0053] 1.5 g of carbon fiber was added to 55 mL of Tris-HCl buffer with a pH of 8.5, stirred evenly, 0.7 g of dopamine was added, stirred for 4 h, filtered, washed with deionized water 3 times, and dried in an oven at 70 °C for 10 min to obtain modified carbon fiber.
[0054] Example 3 The composite gel is prepared by the following steps: 5 g of potassium hydroxide was added to 50 mL of deionized water and stirred evenly. 3 mL of acrylic acid, 0.1 g of N,N-methylenebisacrylamide and 0.1 g of ammonium persulfate were added and stirred for 10 min. Then, 2.5 g of lignin, 1.5 g of modified graphene oxide prepared in Example 1 and 2 g of modified carbon fiber prepared in Example 2 were added. The temperature was raised to 75 ° C, ultrasonicated at 50 KHz for 3 h, and dried in an oven at 70 ° C for 20 min to obtain a composite gel.
[0055] Comparative Example 5 The difference between this comparative example and Example 3 is that the modified graphene oxide prepared in Example 1 is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 3.
[0056] Comparative Example 6 The difference between this comparative example and Example 3 is that the modified graphene oxide prepared in Example 1 is replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 3.
[0057] Comparative Example 7 The difference between this comparative example and Example 3 is that the modified carbon fiber prepared in Example 2 is replaced by the material prepared in Comparative Example 3, and the remaining steps are synchronized with Example 4.
[0058] Comparative Example 8 The difference between this comparative example and Example 3 is that the modified carbon fiber prepared in Example 2 is replaced by the material prepared in Comparative Example 4, and the remaining steps are synchronized with Example 3.
[0059] Comparative Example 9 The difference between this comparative example and Example 3 is that no lignin is added, and the remaining steps are the same as Example 3.
[0060] 1.5 g of the modified graphene oxide prepared in Example 1 and 2 g of the modified carbon fiber prepared in Example 2 were mixed to obtain a composite.
[0061] Example 4 A method for preparing a SCR denitration catalyst comprises the following steps: S1. The composite gel prepared in Example 3, the metal nitrate complex and deionized water were mixed and stirred at a rate of 200 r / min for 30 min to obtain a slurry; Wherein, the amount ratio of the composite gel prepared in Example 3, the metal nitrate complex and deionized water is 5g:4g:100mL; The metal nitrate complex is prepared by mixing manganese nitrate and copper nitrate in a mass ratio of 0.5:4; S2. The pretreated nickel foam is impregnated into the slurry, the temperature is raised to 30° C., stirred at 500 r / min for 2 h, calcined, and cooled to room temperature to obtain an SCR denitration catalyst.
[0062] Among them, the calcination temperature is 700°C and the calcination time is 5h.
[0063] Example 5 A method for preparing a SCR denitration catalyst comprises the following steps: S1. The composite gel prepared in Example 3, the metal nitrate complex and deionized water were mixed and stirred at a rate of 200 r / min for 30 min to obtain a slurry; The ratio of the composite gel, metal nitrate complex and deionized water prepared in Example 3 is 5.5 g:4.5 g:110 mL; The metal nitrate complex is prepared by mixing manganese nitrate and copper nitrate in a mass ratio of 1:4.5; S2. The pretreated nickel foam is impregnated into the slurry, the temperature is raised to 35° C., stirred at 550 r / min for 3 h, calcined, and cooled to room temperature to obtain an SCR denitration catalyst.
[0064] The calcination temperature is 750°C and the calcination time is 6.5h.
[0065] Example 6 A method for preparing a SCR denitration catalyst comprises the following steps: S1. The composite gel prepared in Example 3, the metal nitrate complex and deionized water were mixed and stirred at a rate of 200 r / min for 30 min to obtain a slurry; The ratio of the composite gel, metal nitrate complex and deionized water prepared in Example 3 is 6 g: 5 g: 120 mL; The metal nitrate complex is prepared by mixing manganese nitrate and copper nitrate in a mass ratio of 1.5:5; S2. The pretreated nickel foam is impregnated into the slurry, the temperature is raised to 40° C., stirred at 600 r / min for 4 h, calcined, and cooled to room temperature to obtain an SCR denitration catalyst.
[0066] Among them, the calcination temperature is 800°C and the calcination time is 8h.
[0067] Comparative Example 10 The difference between this comparative example and Example 5 is that the composite gel prepared in Example 3 is replaced by the material prepared in Comparative Example 5, and the remaining steps are the same as Example 5.
[0068] Comparative Example 11 The difference between this comparative example and Example 5 is that the composite gel prepared in Example 3 is replaced by the material prepared in Comparative Example 6, and the remaining steps are the same as Example 5.
[0069] Comparative Example 12 The difference between this comparative example and Example 5 is that the composite gel prepared in Example 3 is replaced by the material prepared in Comparative Example 7, and the remaining steps are the same as Example 5.
[0070] Comparative Example 13 The difference between this comparative example and Example 5 is that the composite gel prepared in Example 3 is replaced by the material prepared in Comparative Example 8, and the remaining steps are the same as Example 5.
[0071] Comparative Example 14 The difference between this comparative example and Example 5 is that the composite gel prepared in Example 3 is replaced by the material prepared in Comparative Example 9, and the remaining steps are the same as Example 5.
[0072] The performance of the SCR denitration catalysts prepared in Examples 4-6 and Comparative Examples 10-14 was tested; Catalytic performance test: The SCR denitration catalyst prepared above was tested on a fixed bed system with continuous flow of reaction gas at a reaction space velocity of 30000 mL g -1 ·h -1The reaction gas composition was 800ppm NO, 800ppm NH3, 5vol% O2, 200ppm SO2, 3vol% H2O, and the balance gas was N2. Before the test, the catalyst sample was pretreated at 200℃ high-purity N2 for 1h, cooled to room temperature, and NO, NH3 and O2 were turned on to adsorb the catalyst to saturation. Then the temperature was raised to the target temperature. The KM9106 flue gas analyzer produced by Kane Company of Germany was used to detect the inlet and outlet NO at 80℃, 110℃, 140℃, 170℃, and 200℃, respectively. x The concentration of NO, denitrification efficiency = [(C0-C) / C0] × 100%. C0 is NO x Inlet concentration, C is NO x Outlet concentration.
[0073] Mechanical strength test: The SCR denitration catalyst prepared above was placed in clean water, soaked for 30 minutes, taken out, and dried at 120°C. The dried denitration catalyst was placed in a sulfuric acid solution with a pH of 2, soaked for 30 minutes, taken out, dried at 120°C, and placed in a muffle furnace at 500°C for calcination for 5 hours. According to the national standard GB / T 1964-2023 "Test method for room temperature compression strength of porous ceramics", the longitudinal strength and axial strength were measured; the results are shown in Table 1 below: Table 1
[0074] It can be seen from the data in Table 1 that the modified graphene oxide prepared by synthesizing cerium-silicon composite nanoparticles on the surface of the monolayer graphene oxide in Comparative Example 10 is used to prepare the SCR denitration catalyst, and its denitration efficiency decreases. This may be because the cerium-silicon composite nanoparticles synthesized on the surface of the monolayer graphene oxide have higher catalytic reaction activity at medium and low temperatures, thereby improving the denitration efficiency of the denitration catalyst at medium and low temperatures, while the monolayer graphene oxide lacks cerium-silicon composite nanoparticles and cannot achieve this effect, so the denitration efficiency decreases.
[0075] In Comparative Example 11, modified graphene oxide prepared by ethyl silicate was not added, and the denitrification efficiency of the SCR denitrification catalyst prepared decreased. This may be because silicon dioxide and cerium oxide are chemically bonded, which improves the binding force of cerium oxide in the monolayer graphene oxide and improves the denitrification efficiency of the denitrification catalyst. Therefore, the denitrification efficiency of the SCR denitrification catalyst prepared by not adding modified graphene oxide prepared by ethyl silicate decreased.
[0076] In Comparative Example 12, the pretreated carbon fiber is replaced with modified carbon fiber prepared from carbon fiber, which is used to prepare the SCR denitration catalyst. Its denitration efficiency and mechanical properties are reduced. This may be because dopamine can self-polymerize on the surface of the carbon fiber to form polydopamine, so that the carbon fiber carries a large number of phenolic hydroxyl groups, which is beneficial to the synthesis of zinc-based metal organic skeletons on the surface of the carbon fiber, thereby improving the denitration efficiency of the denitration catalyst. However, the modified carbon fiber in Comparative Example 12 lacks a dopamine adhesion layer and cannot achieve this effect. Therefore, the denitration efficiency and mechanical properties are reduced.
[0077] Comparative Example 13 does not synthesize a zinc-based metal-organic skeleton on the surface of the pretreated carbon fiber, and is used to prepare an SCR denitrification catalyst, and its denitrification efficiency decreases. This may be because the zinc-based metal-organic skeleton is synthesized on the surface of the pretreated carbon fiber to increase the contact area between the carbon fiber and the active component and enhance the strength. The synthesized zinc-based metal-organic skeleton has a larger porosity, which increases the contact area with nitrogen oxides and improves the denitrification efficiency of the denitrification catalyst. Comparative Example 13 lacks a zinc-based metal-organic skeleton and cannot achieve this effect. Therefore, the denitrification efficiency and mechanical properties decrease.
[0078] In Comparative Example 14, the composite gel prepared without adding lignin was used to prepare the SCR denitrification catalyst, and its denitrification efficiency and mechanical properties decreased. This may be because the slurry formed by the composite gel and the metal nitrate complex was adsorbed into the porous structure of the nickel foam, and then carbonized at high temperature. The skeleton lignin of the composite gel was thermally decomposed to form a carbon-carbon network structure to improve the mechanical strength of the denitrification catalyst, and the carbon elements formed by the thermal decomposition of lignin can also combine with metal ions and be distributed in the porous structure of the nickel foam in the form of metal carbides, thereby increasing the force on the active components and avoiding the migration and precipitation of the active components. However, Comparative Example 14 lacks a gel network structure and cannot achieve this effect, so the denitrification efficiency and mechanical strength are reduced.
[0079] The data in Table 1 show that the SCR denitration catalysts prepared in Examples 4-6 meet the test performance requirements, while the SCR denitration catalysts prepared in Comparative Examples 10-14 do not meet the performance requirements, indicating that the SCR denitration catalysts prepared in the present invention have good medium and low temperature denitration performance.
[0080] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0081] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the defined scope, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a SCR denitration catalyst, characterized in that: The following steps are involved: S1. Mixing the composite gel, the metal nitrate complex and deionized water, stirring to obtain a slurry; The ratio of the composite gel, the metal nitrate complex and the deionized water is (5-6) g: (4-5) g: (100-120) mL; S2. The pretreated nickel foam is impregnated into the slurry, heated to 30-40°C, stirred at 500-600r / min for 2-4h, calcined, and cooled to room temperature to obtain an SCR denitration catalyst; The composite gel is obtained by mixed reaction of modified graphene oxide, modified carbon fiber, initiator, acrylic acid, lignin and cross-linking agent; The modified graphene oxide is obtained by ultrasonically exfoliating graphene oxide, mixing with ethyl silicate and cerium chloride heptahydrate, and then sintering. The modified carbon fiber is prepared by modifying the surface of the carbon fiber with dopamine and then reacting the carbon fiber with a zinc source, 2-aminobenzothiazole and 2-methylimidazole dimethylimidazole.
2. The method for preparing an SCR denitration catalyst according to claim 1, characterized in that: In step S1, the metal nitrate complex is prepared by mixing manganese nitrate and copper nitrate in a mass ratio of (0.5-1.5):(4-5).
3. The method for preparing an SCR denitration catalyst according to claim 1, characterized in that: In step S2, the calcination temperature is 700-800°C, and the calcination time is 5-8h.
4. The method for preparing an SCR denitration catalyst according to claim 1, characterized in that: The graphene oxide particle size is 0.1-2 μm; the ultrasonic power is 40-60 KHz, and the ultrasonic time is 20-40 min.
5. The method for preparing an SCR denitration catalyst according to claim 1, characterized in that: The sintering temperature is 450-550° C., and the sintering time is 4-6 hours.
6. The method for preparing an SCR denitration catalyst according to claim 1, characterized in that: The zinc source is selected from any one of zinc nitrate hexahydrate, zinc chloride and zinc acetate.
7. The method for preparing an SCR denitration catalyst according to claim 1, characterized in that: The initiator is ammonium persulfate; the cross-linking agent is N,N-methylenebisacrylamide.
8. The method for preparing an SCR denitration catalyst according to claim 1, characterized in that: The carbon fiber has a length of 1-3 μm and a diameter of 20-30 nm.
9. The method for preparing an SCR denitration catalyst according to claim 1, characterized in that: The pretreated nickel foam is specifically prepared by the following steps: The nickel foam is soaked in an acetone solution for 10-20 minutes, taken out, washed, and then soaked in dilute hydrochloric acid with a concentration of 2-4 mol / L for 10-20 minutes, taken out, washed, and dried to obtain a pretreated nickel foam.
Citation Information
Patent Citations
Low-temperature smoke denitration SCR (silicon controlled rectifier) catalyst and preparation method
CN102114424A
Low-temperature high-activity flue gas denitrification catalyst and preparation thereof
CN104941630A
Dispersion method of graphene
CN109205603A
Rigid-flexible ZIF-8 / dopamine synergistically enhanced paper-based friction material and preparation method thereof
CN113445360A
Rare earth modified Mn-Fe bimetallic composite molecular sieve denitration catalyst and preparation method thereof
CN114272948A
Cited By
Preparation method of anti-poisoning SCR denitration catalyst
CN120205174A